The impact of primary school nutrition policy on the school food environment: a systematic review - Grigsby-Duffy, Lily; Brooks, Ruby; Boelsen-Robinson, Tara; Blake, Miranda R; Backholer, Kathryn; Palermo, Claire; Peeters, Anna (Health promotion international, 2022)
School nutrition policies that aim to address unhealthy diets have been introduced in many countries. This systematic review aimed to synthesize the international literature to determine the impact (overall and by socioeconomic position [SEP]) of primary school nutrition policies on the availability of foods and beverages in schools. Seven databases were searched using keywords and medical subject headings related to nutrition policies and schools. Studies that reported on the impact of implemented school nutrition policies on food and beverage availability within primary schools were included. Eighteen studies (reported across 20 papers) were included. Fifteen of the included studies reported some positive impacts of policies, including increased availability of healthier foods and decreased availability of less healthy foods. Five studies focused specifically on schools in low-income communities and a further three specifically compared schools by SEP, with mixed findings. Two studies reported on factors influencing policy implementation, reporting a lack of financial resources as a barrier to schools offering a wider selection of healthy foods and additional school resources as increasing the likelihood of offering healthy foods. School nutrition policies appear to be effective at improving the healthiness of foods and beverages available at schools. Furthermore, the results suggest that well-implemented school nutrition policies that improve the healthiness of foods available are unlikely to exacerbate the socioeconomic gradient of poor nutrition. However, the number of studies that reported results by SEP limits drawing strong conclusions regarding equity impacts and we strongly recommend further studies analyze their findings according to SEP.School nutrition policies that aim to address unhealthy diets have been introduced in many countries. This systematic review aimed to synthesize the international literature to determine the impact (overall and by socioeconomic position [SEP]) of primary school nutrition policies on the availability of foods and beverages in schools. Seven databases were searched using keywords and medical subject headings related to nutrition policies and schools. Studies that reported on the impact of implemented school nutrition policies on food and beverage availability within primary schools were included. Eighteen studies (reported across 20 papers) were included. Fifteen of the included studies reported some positive impacts of policies, including increased availability of healthier foods and decreased availability of less healthy foods. Five studies focused specifically on schools in low-income communities and a further three specifically compared schools by SEP, with mixed findings. Two studies reported on factors influencing policy implementation, reporting a lack of financial resources as a barrier to schools offering a wider selection of healthy foods and additional school resources as increasing the likelihood of offering healthy foods. School nutrition policies appear to be effective at improving the healthiness of foods and beverages available at schools. Furthermore, the results suggest that well-implemented school nutrition policies that improve the healthiness of foods available are unlikely to exacerbate the socioeconomic gradient of poor nutrition. However, the number of studies that reported results by SEP limits drawing strong conclusions regarding equity impacts and we strongly recommend further studies analyze their findings according to SEP.